A chitosan/acellular matrix-based neural graft carrying mesenchymal stem cells to promote peripheral nerve repair - Zhifa Zhang; Molin Li; Gang Cheng; Peng Wang; Chunhui Zhou; Yang Liu; Xiaofeng Duan; Jing Wang; Fang Xie; Yaqiong Zhu; Jianning Zhang (Stem Cell Research & Therapy)
Abstract Background Treatment of peripheral nerve defects is a major concern in regenerative medicine. This study therefore aimed to explore the efficacy of a neural graft constructed using adipose mesenchymal stem cells (ADSC), acellular microtissues (MTs), and chitosan in the treatment of peripheral nerve defects. Methods Stem cell therapy with acellular MTs provided a suitable microenvironment for axonal regeneration, and compensated for the lack of repair cells in the neural ducts of male 8-week-old Sprague Dawley rats. Results In vitro, acellular MTs retained the intrinsic extracellular matrix and improved the narrow microstructure of acellular nerves, thereby enhancing cell functionality. In vivo neuroelectrophysiological studies, gait analysis, and sciatic nerve histology demonstrated the regenerative effects of active acellular MT. The Chitosan + Acellular-MT + ADSC group exhibited superior myelin sheath quality and improved neurological and motor function recovery. Conclusions Active acellular-MTs precellularized with ADSC hold promise as a safe and effective clinical treatment method for peripheral nerve defects. Graphical abstract